Panti Asuhan Putri Di Kota Pekanbaru Dengan Pendekatan Arsitektur Perilaku - Anggilina, Oktavia; Susilawaty, Mira Dharma; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Orphanage as a home or residence used to care, care for orphans, orphans and orphans. In fulfilling the physical,mental and social needs that require the role of companion as a substitute in creating the character especially in thefemale children. There is not much facilities and infrastructure to support the needs of the life of the orphanage. Byoptimizing the growth with affection, comfort, coaching and carers in formal education, morals and entrepreneurship inaccordance with the girl character of prosperous and independent. It becomes the background of this design. So thisdesign illustrates the application of Behavioral Architecture. The research method used is behavioral mapping method(behavioral mapping) which applied to the building. Data collection methods such as field data collection, literaturestudy and empirical study. Application of Child Behavior to the building concept used in this design is familytogetherness which can provide love, togetherness and provide a place for learning activities, playing, as well asdeveloping talent for children. Can be found through the form of building which is a transformation of child behavior,the colors used give the impressionof femiliar, soft and safe use of material according to the child’s behavior, creatingthe impression of protecting from the building.Keywordrs : Orphanage, Character, Children, Behavioral Architecture, Family togetherness